A personal communicator of the vocally handicapped - REILLY, RICHARD (IEEE, 1992)
An affordable personal communicator which allows full control of the voice has been designed and developed. The aid employs coded digitised speech in an efficient manner, coupled with specif- hardware in an attempt to address the problems which normally beset such communicators. Speech is recorded, digitised and compressed under ADPCM from 12 to 4-bits. The compressed waveform is transferred into a portable handheld, discreet playback unit, under the control of specif= graphic interface software, allowing complete customisation of the handheld unit for the user or application.
PUBLISHED
Keywords: Administrative Staff Authors